1998
DOI: 10.1084/jem.188.4.725
|View full text |Cite
|
Sign up to set email alerts
|

Cysteine Protease Inhibitors Cure an Experimental Trypanosoma cruzi Infection

Abstract: Trypanosoma cruzi is the causative agent of Chagas' disease. The major protease, cruzain, is a target for the development of new chemotherapy. We report the first successful treatment of an animal model of Chagas' disease with inhibitors designed to inactivate cruzain. Treatment with fluoromethyl ketone–derivatized pseudopeptides rescued mice from lethal infection. The optimal pseudopeptide scaffold was phenylalanine-homophenylalanine. To achieve cure of infection, this pseudopeptide scaffold was incorporated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
340
0
16

Year Published

2001
2001
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 372 publications
(369 citation statements)
references
References 30 publications
(41 reference statements)
5
340
0
16
Order By: Relevance
“…Enhanced NO generation resulted upon incubating cystatin with IFN-␥-activated mouse peritoneal macrophages in vitro, and the leishmanicidal activity acquired correlated with the induction of NO production. It may be mentioned that Engel et al (30) showed a parasiticidal effect of synthetic cysteine protease inhibitors on intracellular Trypanosoma cruzi by inactivation of cruzain, a major protease of the parasite. The reason cystatin may induce an increase in NO synthesis from activated macrophages remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Enhanced NO generation resulted upon incubating cystatin with IFN-␥-activated mouse peritoneal macrophages in vitro, and the leishmanicidal activity acquired correlated with the induction of NO production. It may be mentioned that Engel et al (30) showed a parasiticidal effect of synthetic cysteine protease inhibitors on intracellular Trypanosoma cruzi by inactivation of cruzain, a major protease of the parasite. The reason cystatin may induce an increase in NO synthesis from activated macrophages remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…4,5,16,17 Vinyl sulfone inhibitor 38 was prepared via a Horner-Wadsworth-Emmons olefination (Scheme 3). Kinetic analysis of the vinyl sulfone inhibitor, surprisingly, indicated no time dependence and was consistent with competitive reversible inhibition (Figure 4a).…”
Section: Conversion Of Substrates Into Inhibitorsmentioning
confidence: 99%
“…[11][12][13][14] Addition of a cruzain inhibitor to cultures of mammalian cells exposed to trypomastigotes or to mammalian cells already infected with T. cruzi amastigotes blocks replication and differentiation of the parasite, thus interrupting the parasite life cycle. [15][16][17][18][19][20][21] Several groups have demonstrated that irreversible inhibition of cruzain by small molecules eradicates infection of the parasite in cell culture and animal models. 17,[22][23][24][25] Irreversible inhibitors that contain an electrophilic functional group, such as vinyl sulfones, fluoro methyl ketones, aziridines or nitriles, covalently bind to cruzain via nucleophilic attack of the active site cysteine, 26 showing good inhibition activity.…”
Section: Introductionmentioning
confidence: 99%
“…[15][16][17][18][19][20][21] Several groups have demonstrated that irreversible inhibition of cruzain by small molecules eradicates infection of the parasite in cell culture and animal models. 17,[22][23][24][25] Irreversible inhibitors that contain an electrophilic functional group, such as vinyl sulfones, fluoro methyl ketones, aziridines or nitriles, covalently bind to cruzain via nucleophilic attack of the active site cysteine, 26 showing good inhibition activity. 27,28 In fact, to date, only irreversible inhibitors of cruzain have successfully cured parasitic infection, 23 implying that tight binding to the enzyme may be essential.…”
Section: Introductionmentioning
confidence: 99%